Think Talk Write (TTW) Learning Model by Using Realia Towards Mathematical Communication Ability of Elementary School Students (Journal of Primary Education, 2019)
The purpose of this study was to analyze the effectiveness of Think Talk Write learning with realia media compared to expository learning on students' mathematical communication ability. This study applied a quantitative research design with a quasi-experimental nonequivalent control group design. Sampling was done by using simple random sampling technique; therefore, the sample obtained was SD N 9 Panggang as the experimental class and SD N 2 Bulu as the control class with a total of 78 students. The data collection technique used in this study was the achievement test of learning outcomes by comparing the test scores of the two groups by using the z-test and t-test. The results showed that the Think Talk Write learning with realia media was effective in improving students' mathematical communication ability as indicated by the acquisition of z-test results obtained by zcount > ztable = 2.868 > 0.174 which means that students who were taught by using Think Talk Write had achieved classical completeness by 75%. These results were supported by the results of the independent sample t-test which showed that the Sig. (2-tailed) 0.000 smaller than 0.05, which means that the average value of mathematical communication ability of students who follow the Think Talk Write learning with realia media was higher than the expository. Think Talk Write learning with realia media can be used as an easy solution for teachers to improve students 'mathematical communication ability.